EFEKTIVITAS PENERAPAN E-GOVERNMENT MELALUI SISTEM E-TILANG PADA SATUAN POLISI LALU LINTAS (SATLANTAS) POLRESTA PEKANBARU - Mutia Riska; Hasim As'ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
At present, public demand requires the government to renew the public service, which is a technology-based service (E-Government). The development of E-Government in various areas is marked by the availability of applications and information systems that support the execution of office tasks, one of which is being implemented at Pekanbaru Traffic Police Agency aimed at developing E-Government through the E-Tilang system. The problems raised by the researchers in this study were regarding the E-Tilang System Implementation Effectiveness and factors that hinder the effectiveness of E-Tilang System implementation. This research method is a qualitative method with a case study approach. The concept of theory used is the theory of effectiveness with several indicators, namely the achievement of objectives, the ability to perform tasks, and the appropriateness of input and output. In this study the author will analyze the problem through data obtained from interviews, observations and documentation. The results show that the use of E-Traffic is not yet effective. It is evident from the public that they are not fully aware of the e-ticket system, the lack of information from officials about the E-Tilang system, and the extortion that officials still face during traffic violations. In an E-Tilang application, the author noted several factors that impede, from an officer, a frequent network interruption that prevents the sending of tilang fines and Briva numbers to violators. Whereas the offenders lack the socialization associated with the E-Tilang system from officials to offenders so that the public is still confused by the mechanism of the E-Tilang System, as well as the poor conduct of the executor found in the levy found by the executor to the infringer causing the implementation of the E - Tilang system effective again. Keywords: Effectiveness, E-Government, E-Tilang System